Mechanical evaluation of two loop-fastening methods for stainless steel wire - Bar-Am, Y.; Klement, E.; Fourman, V.; Shahar, R. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
The clinical use of stainless steel wire in veterinary orthopaedics is common, and occurs in diverse situations. One of the most common uses of stainless steel wire is the fabello-tibial suture to stabilize the cranial cruciate deficient knee (10). Numerous reports have appeared in the literature, describing biomechanical aspects of the use of stainless steel wire. The purpose of the study presented herein was to compare the strength and performance of two methods used to fasten loops of stainless steel wire: the traditional twistknot method and the crimp-clamp method. Both loopfastening methods were evaluated with two diameters of wire (1.0 mm and 1.2 mm). Both static and dynamic (cyclical) testing procedures were performed. Using a materials testing machine maximum tensile strength (load to failure), loop elongation, mode of loop failure and location of loop failure were recorded. The results of the study demonstrate that loops fastened with the crimp clamp method resulted in higher load to failure than the traditional twist knot method.
Keywords: Wire loops; twist knot; crimp clamp; load to failure; loop elongation